Construction and characterization of a reverse genetics system of bovine parainfluenza virus type 3c as a tool for rapid screening of antivirals in vitro - Han, Yu; Lu, Kejia; Zhang, Riteng; Wei, Xi; Guo, Hanwei; Tong, Lina; Wang, Xinglong; Xiao, Sa; Liu, Haijin; Yang, Zengqi (Frontiers in Veterinary Science, 2024)
Bovine parainfluenza virus type 3 (BPIV3) is a key pathogen associated with bovine respiratory disease complex (BRDC). However, its specific pathogenesis mechanisms have not been fully elucidated. Reverse genetics provides a useful method for understanding the pathogenic mechanism of BPIV3. To ensure the functionality of the rescue platforms, we first constructed a minigenome (MG) system of BPIV3 utilizing a 5-plasmid system in this investigation. Then, a full-length infection clone of BPIV3 was obtained from the SX-2021 strain, and different methods were employed to identify the rescued virus. Additionally, we recovered a recombinant BPIV3 using the reverse genetics system that could express enhanced green fluorescence protein (eGFP). Through the growth curve assays, the replicate capability of rBPIV3-SX-EGFP was found to be similar to that of the parental virus. Subsequently, the rBPIV3-SX-EGFP was used to determine the antiviral activity of ribavirin. The results showed that ribavirin had an anti-BPIV3 effect in MDBK cells. In conclusion, the successful development of a reverse genetic system for the SX-2021 strain establishes a foundation for future studies on BPIV3, including investigations into its pathogenic mechanism, gene function, and antiviral screening properties.